The Formation of the Contemporary Renewable Energy Sector and its Role in the Industry Development - Akhmetshin, Elvir; Zhiltsov, Sergey; Dmitrieva, Anna; Plotnikov, Andrei; Kolomeytseva, Angelina (International Journal of Energy Economics and Policy, 2019)
Currently, renewable energy is one of the core issues brought up monthly on the global market. The created green energy policy and support of the most advanced countries are aimed at its development. State-of-the-art technology, necessary scope of knowledge, and optimal conditions for using renewable sources of energy altogether are the factors for focusing on the development of the industry. The core purpose of the research was to reveal facts of the current formation of the renewable energy sector. As a result of the research, we found out that the renewable energy sector is currently achieving its peak of popularity. The issue is of worldwide relevance, and the leading countries focus their efforts on supporting the industry, while municipalities extensively implement such facilities in large cities. Renewable energy resources are also used in such areas as the transportation, cooling, heating, and energy industry, and many others. Keywords: Renewable energy, Biofuel, Municipal energy sector, Power generation. JEL Classifications: K3, Q42, Q48. DOI: https://doi.org/10.32479/ijeep.8229